The loss of happiness in market democracies - Lane, Robert E., 1917-2017 (Yale ISPS series., 2000)
"Drawing on extensive research in such fields as quality of life, economics, politics, sociology, psychology, and biology, Robert E. Lane presents a challenging thesis. He shows that the main sources of well-being in advanced economies are friendships and a good family life and that, once one is beyond the poverty level, a larger income contributes almost nothing to happiness. In fact, as prosperity increases, there is a tragic erosion of family solidarity and community integration, and individuals become more and more distrustful of each other and their political institutions. Lane urges that we alter our priorities so that we increase our levels of companionship even at the risk of reducing our income."--Book jacket.